Implementation of the Non-Tax State Revenue Policy on the Use of Forest Areas in Controlling Mining Activities in Forest Areas - Almansuri, Anton; Wicaksana, Harits Hijrah; Mariam, Siti; Waluyo, Surryanto Djoko (Dinasti Publisher, 2025)
This study examines the implementation of Non-Tax State Revenue – Forest Area Utilization (PNBP-PKH) as an instrument for controlling mining in forest areas. The background is the high economic contribution—PNBP-PKH reached IDR 2.42 trillion (2021), IDR 2.88 trillion (2022), and IDR 2.55 trillion (2023)—but accompanied by net deforestation of 104,000 ha (2021–2022). A qualitative descriptive method was used through interviews with six key informants from the government and business actors. The results show that impact category-based tariffs (L1–L3) encourage early reclamation, but are hampered by institutional coordination, regional verification capacity, unintegrated cross-ministerial information systems, and suboptimal business actors. Several companies experience administrative delays and spatial data discrepancies. The conclusion is that digital integration, increased regional technical capacity, and simplified procedures are needed to strengthen the dual role of PNBP-PKH as a fiscal and environmental policy.